Repression and autocracy as Russia heads into State Duma elections - Sabine Fischer (Stiftung Wissenschaft und Politik (SWP), 2021)
Russia is experiencing a wave of state repression ahead of parliamentary elections on 19 September 2021. The crackdown is unusually harsh and broad, extending into previously unaffected areas and increasingly penetrating the private sphere of Russian citizens. For years the Russian state had largely relied on the so-called "power vertical" and on controlling the information space through propaganda and marginalisation of independent media. The political leadership, so it would appear, no longer regards such measures as sufficient to secure its power and is increasingly resorting to repression. The upshot is a further hardening of autocracy. Even German NGOs are experiencing growing pressure from the Russian state. This trend cannot be expected to slow, still less reverse in the foreseeable future.
Keywords: 320